Non-intrusive flow diagnostics for unsteady inlet flow distortion measurements in novel aircraft architectures - Doll, Ulrich; Migliorini, Matteo; Baikie, Joni; Zachos, Pavlos K.; Röhle, Ingo; Melnikov, Sergey; Steinbock, Jonas; Dues, Michael; Kapulla, Ralf; MacManus, David G.; Lawson, Nicholas J. (Elsevier, 2022)
Inlet flow distortion is expected to play a major role in future aircraft architectures where complex air induction systems are required to couple the engine with the airframe. The highly unsteady distortions generated by such intake systems can be detrimental to engine performance and were previously linked with loss of engine stability and potentially catastrophic consequences. During aircraft design, inlet flow distortion is typically evaluated at the aerodynamic interface plane, which is defined as a cross-flow plane located at a specific upstream distance from the engine fan. Industrial testing currently puts more emphasis on steady state distortions despite the fact that, historically, unsteady distortions were acknowledged as equally important. This was partially due to the limitations of intrusive measurement methods to deliver unsteady data of high spatial resolution in combination with their high cost and complexity. However, as the development of aircraft with fuselage-integrated engine concepts progresses, the combination of different types of flow distortions is expected to have a strong impact on the engine’s stability margin. Therefore, the need for novel measurement methods able to meet the anticipated demand for more comprehensive flow information is now more critical than ever. In reviewing the capabilities of various non-intrusive methods for inlet distortion measurements, Filtered Rayleigh Scattering (FRS) is found to have the highest potential for synchronously characterising multiple types of inlet flow distortions, since the method has the proven ability to simultaneously measure velocity, static pressure and temperature fields in challenging experimental environments. The attributes of the FRS method are further analysed aiming to deliver a roadmap for its application on ground-based and in-flight measurement environments.
Keywords: Air induction systems; Convoluted diffusers; Inlet flow distortion; Unsteady flow; Propulsion integration; Non-intrusive flow diagnostics; Seeding-free measurements; Laser based flow measurements; Filtered Rayleigh Scattering (FRS)